Kesembuhan Ilahi Eskatologis, Holistik, Dan Pentakostal: Macchia–Vondey Dan Kontribusinya Bagi Diskursus Teologi Indonesia - Christo Antusias Davarto Siahaan (Sekolah Tinggi Teologi Aletheia, 2025)
This paper seeks to enrich the theological discourse on divine healing in Indonesia. Divine healing refers to healing believed to come from the power of God, commonly understood as occurring directly or through miraculous or supernatural means. This practice often involves prayer, speaking words of faith, and similar actions. The current theological conversation on divine healing in the Indonesian context tends to focus on its criticisms, apologetics, biblical studies, and descriptive field research. However, it seldom engages deeply with broader loci of systematic theology. In response, this paper argues that the theological visions of Frank D. Macchia and Wolfgang Vondey offer an understanding of divine healing that is eschatological, holistic, and Pentecostal. Eschatological refers to the manifestation of the Kingdom of God that has already come and will be consummated in the parousia of Jesus Christ. Holistic implies that healing embraces spiritual, psychological, social, biological, economic, ecological, and political dimensions. Pentecostal signifies an emphasis on Spirit baptism and divine healing as a response to God’s call to be restored and to participate in God's restorative mission. The author arrives at this thesis through a threefold literaturebased approach: first, by presenting the ideas of Macchia and Vondey; second, by synthesizing their insights; and third, by articulating their implications.